Effect of Audit Quality, Debt Ratio, Debt Default, Financial Distress on Going Concern Audit Opinions on Consumer Goods Companies Listed on the Indonesia Stock Exchange in 2016-2019 - Ginting, Wenny Anggeresia; Rendy, Rendy; Mansyur, Michelle Livia (Budapest International Research and Critics University, 2021)
The purpose of this study was to determine the effect of audit quality, debt ratio, debt default, financial distress on going concern audit opinions on Consumer Goods Companies listed on the Indonesia Stock Exchange in 2016-2019. This research method is associative research. The population of this study were 51 Consumer Goods Companies listed on the Indonesia Stock Exchange in 2016-2019. The research sample was 16 Consumer Goods Companies listed on the Indonesia Stock Exchange in 2016-2019. Data collection used literature review and documentation. Hypothesis testing is done by multivariate analysis using logistic regression. The results show that audit quality has no effect on going concern audit opinions on Consumer Goods Companies listed on the Indonesia Stock Exchange in 2016-2019. The debt ratio has no effect on going concern audit opinions on Consumer Goods Companies listed on the Indonesia Stock Exchange in 2016-2019. Debt default has no effect on going concern audit opinions on Consumer Goods Companies listed on the Indonesia Stock Exchange in 2016-2019. Financial distress has no effect on going concern audit opinions on Consumer Goods Companies listed on the Indonesia Stock Exchange in 2016-2019. Audit quality, debt ratio, debt default, financial distress effect going concern audit opinions on Consumer Goods Companies listed on the Indonesia Stock Exchange in 2016-2019.